A Comprehensive Review on Nanoparticles: Pivotal Element of Nanotechnology in Medicine and Healthcare System - Kanabar Vishvesh; Patel Vipul; Marupati Siddhartha (E3S Web of Conferences)
In pursuit advancing fundamental human rights, particularly in the realm of healthcare, technological innovation has consistently played a crucial role. The intersection of technology and healthcare has yielded significant benefits, ensuring the availability of healthcare that is not only high-quality and timely but also acceptable and reasonably priced. Technological advancements, especially in the domain of nanoscience, have given rise to a novel class of nanostructures, each possessing distinct qualities that contribute to their remarkable applicability. Nanotechnology, since its inception, has exerted a profound impact on healthcare, catalyzing transformative changes and yielding improved outcomes. Key Points: Human Rights and Healthcare: Access to high-quality, timely, and affordable healthcare is considered a fundamental human right. Technological advancements, particularly in nanotechnology. New Nanostructures: Recent developments in nanoscience have given rise to a unique class of nanostructures. These structures exhibit distinct qualities that contribute to their exceptional applicability in healthcare settings. Transformative Impact: Nanotechnology has significantly transformed the healthcare landscape, leading to advancements and improved outcomes across various medical disciplines. Global Adoption: The widespread integration in nanotechnology into healthcare practices on a global scale. This adoption has been facilitated by substantial research conducted in diverse healthcare-related fields. Technological Research: Ongoing research efforts continue to explore the potential of nanotechnology in healthcare. These endeavors aim to uncover new possibilities and applications, further enhancing the impact of nanotechnology on medical practices. The synergy between nanotechnology and healthcare exemplifies the potential of innovative technologies to address fundamental human needs. Nanomedicine, involves the application of nanotechnology and related nano carriers / nano systems to enhance various aspects of medical practice. This rapidly expanding discipline has brought about significant advancements in the detection, prevention, and treatment of illnesses. Notably, certain nano systems have proven to be more effective than conventional methods, particularly in theranostic applications. Theranostics involves combining diagnostic capabilities with therapeutic functionalities, and nanomedicine has demonstrated promising potential for same.